Analysis of the KUCA ADS benchmarks with diffusion theory. (November 2017) - van Rooijen, W.F.G.; Endo, T.; Chiba, G.; Pyeon, C.H.
Abstract: This manuscript discusses the analysis of the KUCA-A ADS with deterministic theory, specifically diffusion theory. The KUCA-A ADS is a small, thermal-spectrum ADS. For the series of experiments in this manuscript, a DT fusion neutron source was used (14 MeV neutrons). Several sets of KUCA ADS experiments are available as international benchmarks. In our analysis, we calculated the multiplication factor, prompt neutron decay constant ( α -eigenvalue), and used time-dependent diffusion theory to analyze pulsed neutron operation of the KUCA-A ADS. The results are that the multiplication factor is generally well predicted as long as the void regions in the core remain of a limited extent. The time-eigenvalue ( α -eigenvalue) is also well predicted, and knowledge of the α -mode can be effectively used in the selection of measurement data for curve fitting methods.